Correction: Fine tuning of ferromagnet/antiferromagnet interface magnetic anisotropy for field-free switching of antiferromagnetic spins. Issue 37 (22nd September 2020) - Ślęzak, M.; Dróżdż, P.; Janus, W.; Nayyef, H.; Kozioł-Rachwał, A.; Szpytma, M.; Zając, M.; Menteş, T. O.; Genuzio, F.; Locatelli, A.; Ślęzak, T.
Abstract : Correction for 'Fine tuning of ferromagnet/antiferromagnet interface magnetic anisotropy for field-free switching of antiferromagnetic spins' by M. Ślęzak et al., Nanoscale, 2020, DOI: ; 10.1039/d0nr04193a .